2018
DOI: 10.1002/bmc.4219
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of evodiamine and its four metabolites in rat plasma by LC–MS/MS and its application to a pharmacokinetic study

Abstract: A simple and sensitive liquid chromatography tandem mass spectrometry method was validated for simultaneous quantification of evodiamine and its metabolites 10-hydroxyevodiamine (M1), 18-hydroxyevodiamine (M2), 10-hydroxyevodiamine-glucuronide (M3) and 18-hydroxy- evodiamine-glucuronide (M4) in rat plasma for the first time. The analytes were extracted with acetonitrile and separated on a C column within 3 min. The detection was achieved in positive selected reaction monitoring mode with precursor-to-product t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The radioactivity levels in the plasma reached their maximum level within 1 h of oral administration, which declined in a biphasic manner, with half-times of 1.6 and 78.4 h (84). EVO has also been reported to reach a maximum plasma concentration in rat 3.38 h (T max ) after oral administration (35). EVO is predominantly distributed in the liver, kidney, heart and lungs, where 19 and 63% of orally administered EVO is eliminated in the urine and bile after 24 h, respectively (84).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The radioactivity levels in the plasma reached their maximum level within 1 h of oral administration, which declined in a biphasic manner, with half-times of 1.6 and 78.4 h (84). EVO has also been reported to reach a maximum plasma concentration in rat 3.38 h (T max ) after oral administration (35). EVO is predominantly distributed in the liver, kidney, heart and lungs, where 19 and 63% of orally administered EVO is eliminated in the urine and bile after 24 h, respectively (84).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
“…A previous study demonstrated that EVO is readily susceptible to metabolism, forming hydroxylation metabolites, which exhibit potent cytotoxicity compared with that mediated by EVO (35). Furthermore, another study suggested that the 3-alkylindole moiety on EVO is a potential toxicophore in P450-mediated dehydrogenation reactions (34).…”
Section: Metabolism Komatsu Et Al (84) Demonstrated That [ 3 H] Evo Can Be Converted Into Metabolites In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of GL-V9, although a concentration peak was seen after 0.5 h of oral administration, a second twin peak was recorded after 12 h (in rats), most likely related to the enterohepatic, enteric, or local recycling [60]. A double peak was detected in the plasma concentration–time curves for baicalin, oroxin A (baicalein-7- O -glucoside), baicalein, wogonoside, wogonin, and chrysin when administered in rats, related to enterohepatic, local, or enteric recycling [16,23,32,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100]. In one study in rats, it was claimed that this bi-modal “behavior” was not confirmed experimentally [101], but the authors only measured plasma samples up to 180 min, whereas in order to observe the second peak (at its maximum) at least 6–8 h would often be needed [102,103,104,105], although in other cases a second peak was reported after only two to three hours [106,107,108,109]; in dogs, following i.v.…”
Section: Recyclingmentioning
confidence: 99%
“…Therefore, to support the pharmacokinetic study, development and validation of a simple and sensitive assay is necessary. Due to the high sensitivity and selectivity, UHPLC–MS/MS has received considerable attention, and now it is the most commonly preferred technique for biomedical analysis (Han, Yang, Ding, Ji, & Zhang, 2015; Iqbal, Ezzeldin, Khalil, Alam, & Al‐Rashood, 2018; Wang, Yue, Ai, & Yang, 2018; Yi & Lan, 2020; Zhao, Wu, Liu, Zhang, & Lin, 2014).…”
Section: Introductionmentioning
confidence: 99%